The Role of Serum Uric Acid in Preeclampsia - Amir Taefi; Ashraf Sadat Jamal; Human Delavari (Tehran University of Medical Sciences, 2008)
Objective: The goal of this study was to assess the utility of serum uric acid in preeclampsia diagnosis and its correlation with some maternal and fetal outcomes. Materials and methods: A case-control study was performed on 26 term pregnant women with preeclampsia and 52 normal pregnant women. Serum uric acid, platelet count, hematocrit, gestational age, and birth weight of all patients were measured. Data distribution was assessed with the one sample Kolmogorov-Smirnov test. Mann-Whitney U test was used to assess differences between groups. Correlations between plasma uric acid and other parameters were evaluated with the Spearman's Rho or Pearson correlation test, where appropriated. Receiver-operating characteristics (ROC) curves were used to assess the ability of plasma uric acid to distinguish the preeclampsia from normal subjects. Significance was set at P< 0.05. Results: The mean level of plasma uric acid was 5.8 (+2) mg/dl in cases and 4.9 mg/dl in controls (P=0.04). ROC curve analysis demonstrates the absence of obvious cut off point for plasma uric acid to distinguish preeclampsia. Sensitivity and specificity for uric acid level of 5.5 mg/dl were 61.5% and 78.8%, respectively. There was no significant linear correlation between the plasma uric acid level and other measured parameters in each group. Conclusion: On the basis of our data, the clinical utility of measuring serum uric acid levels in diagnosing preeclampsia is limited.